Breast pain affects the performance of elite female athletes - Brisbine, B. R.; Steele, J. R.; Phillips, E. J.; McGhee, D. E. (Journal of Sports Sciences, 2020)
Although breast pain is problematic for many active women, no published research has investigated breast pain experienced by elite female athletes. This study aimed to examine the extent that mastalgia and exercise-induced breast pain affected the sporting performance of elite female athletes during training and competition. A custom-designed online survey with questions related to sport participation, as well as the frequency, severity and perceived performance effects of mastalgia and exercise-induced breast pain, was distributed to sporting organisations, coaches, medical staff and teams/clubs throughout Australia. Five hundred and forty female athletes competing nationally or internationally across 49 different sports participated in the survey. Sixty-three percent of respondents reported experiencing breast pain associated with their menstrual cycle and 33% reported that this pain worsened during activity. Forty-four percent of athletes reported experiencing exercise-induced breast pain during training or competition. Both types of breast pain were also reported to negatively affect sporting performance (20% and 32%, respectively). Mastalgia associated with the menstrual cycle and exercise-induced breast pain should be acknowledged as potential problems affecting the sporting performance of elite female athletes. Awareness around the impact of breast pain and the development and implementation of breast pain management strategies are essential for this population.